Socioeconomic position and the risk of gastric and oesophageal cancer in the European Prospective Investigation into Cancer and Nutrition (EPIC-EURGAST). - Nagel, G; Linseisen, J; Boshuizen, H; Pera, G; Del Giudice, G; Westert, G; Bueno-de-Mesquita, H; Allen, N; Key, T; Numans, M; Peeters, P; Sieri, S; et al. (2007)
OBJECTIVES: To evaluate the association of socioeconomic position with adenocarcinoma of the oesophagus and stomach. METHODS: The European Prospective Investigation into Cancer and Nutrition (EPIC) cohort comprises about 520 000 participants mostly aged 35-70 years. Information on diet and lifestyle was collected at recruitment. After an average follow-up of 6.5 years, 268 cases with adenocarcinoma of the stomach and 56 of the oesophagus were confirmed. We examined the effect of socioeconomic position on cancer risk by means of educational data and a computed Relative Index of Inequality (RII). In a nested case-control study, adjustment for Helicobacter pylori (H. pylori) infection was performed. RESULTS: Higher education was significantly associated with a reduced risk of gastric cancer [vs lowest level of education, hazard ratio (HR): 0.64, 95% Confidence intervals (CI): 0.43-0.98]. This effect was more pronounced for cancer of the cardia (HR: 0.42, 95% CI: 0.20-0.89) as compared to non-cardia gastric cancer (HR: 0.66, 95% CI: 0.36-1.22). Additionally, the inverse association of educational level and gastric cancer was stronger for cases with intestinal (extreme categories, HR: 0.13, 95% CI: 0.04-0.44) rather than diffuse histological subtype (extreme categories, HR: 0.71 95% CI: 0.37-1.40). In the nested case-control study, inverse but statistically non-significant associations were found after additional adjustment for H. pylori infection [highest vs lowest level of education: Odds ratio (OR) 0.53, 95% CI: 0.24-1.18]. Educational level was non-significantly, inversely associated with carcinoma of the oesophagus. CONCLUSION: A higher socioeconomic position was associated with a reduced risk of gastric adenocarcinoma, which was strongest for cardia cancer or intestinal histological subtype, suggesting different risk profiles according to educational level. These effects appear to be explained only partially by established risk factors.